CHALLENGES PERCEIVED OF STUDENT LEADERS ON COMING OUT AS LGBTQIA+ AT BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Despite significant advancements in LGBTQIA+ rights, individuals continue to face discrimination and challenges when disclosing their sexual orientation or gender identity. This process, known as "coming out," can be both liberating and daunting, with experiences varying widely among individuals. ​ nsvrc.org  Challenges Associated with Coming Out and Gender Identity Disclosure:  Risk of Negative Reactions: Individuals may encounter rejection from family, friends, or community members, leading to strained relationships and emotional distress. ​  Discrimination and Harassment: Disclosing one's identity can result in discrimination in various settings, including employment and educational institutions, as well as potential harassment or abuse. ​ case.edu  Mental Health Implications: Early disclosure, especially before the age of 13, has been linked to higher rates of depression and lower self-esteem, particularly when individuals face physical threats or harm due to their identity. ​  Workplace Considerations: The decision to disclose one's sexual orientation or gender identity in professional environments can be challenging, with concerns about discrimination and career implications. ​  Healthcare Disclosure: Gender-expansive youth often face dilemmas regarding disclosure to healthcare providers, with mixed disclosure associated with higher depression symptoms and lower self-esteem. ​  Recent Developments Impacting LGBTQIA+ Rights:  Policy Changes: Iowa has become the first state to remove gender identity protections from its civil rights law, eliminating "gender identity" as a protected class in areas such as housing, employment, and education. ​ Them  Federal Surveys: The U.S. Census Bureau, under the Trump administration, has sought permission to remove questions about gender identity from its Pulse Survey, aligning with policies that define sex strictly as male or female in official documents. ​ Associated Press  Recognizing and Addressing the Challenges:  Understanding these challenges is crucial for fostering inclusive environments that promote emotional and psychological well-being. Supportive measures include:  Educational Initiatives: Implementing programs that educate communities about LGBTQIA+ issues to reduce stigma and discrimination.​  Policy Development: Establishing policies that protect against discrimination based on sexual orientation and gender identity in all spheres, including employment, education, and healthcare.​  Mental Health Support: Providing accessible mental health services tailored to the unique experiences of LGBTQIA+ individuals.​  Safe Spaces: Creating environments where individuals feel safe and supported in expressing their identities without fear of retribution or harm. This study employs a descriptive research design, targeting seventy (70) LGBTQIA+ student leaders across first to fourth-year college levels. Purposive sampling is utilized to engage this specific group, ensuring that participants possess relevant characteristics to provide rich and diverse data. Data collection is facilitated through a researcher-developed survey questionnaire, structured into three sections: demographic profiles, perceived challenges, and difficulties encountered by LGBTQIA+ student leaders. Ethical considerations are meticulously addressed by obtaining informed consent, ensuring participant confidentiality, and safeguarding participants' rights throughout the research process. ​ The study provides a comprehensive examination of the challenges faced by LGBTQIA+ individuals, revealing insights across various dimensions:​  Social Support: A weighted mean of 3.05 indicates perceived challenges in receiving adequate support after coming out.​  Mental Well-being: With a weighted mean of 3.00, this suggests negative impacts on mental health post-coming out.​  Outness Level: A weighted mean of 2.99 reflects challenges related to fear of judgment and discrimination.​  Gender Identity Challenges:  Social Acceptance: A weighted mean of 3.12 highlights perceived difficulties in social acceptance.​ Educational Environment: A weighted mean of 3.23 underscores challenges within educational settings.​ The overall weighted mean of 3.095 emphasizes the importance of enhancing inclusivity, awareness, and support within social and educational contexts to address these challenges effectively. Addressing the challenges faced by LGBTQIA+ student leaders necessitates a multifaceted approach within educational settings. Key strategies include:​  Implementing Inclusive Data Collection Methods: Developing and administering surveys that capture diverse sexual orientations and gender identities is essential. Educational institutions should thoughtfully consider the necessity and utility of collecting such data, ensuring privacy and security, and utilizing inclusive language that acknowledges the diversity within the LGBTQIA+ community. ​   Establishing LGBTQ+ Student Support Groups: Creating safe spaces within schools where LGBTQ+ students can connect, share experiences, and receive peer support significantly contributes to their well-being. Programs that facilitate community-building and provide resources tailored to LGBTQ+ youth are vital. ​   Conducting Awareness and Education Programs: Implementing curricula that include LGBTQ+ history and contributions fosters an environment of acceptance and respect. Studies have shown that inclusive education leads to better outcomes for LGBTQ+ students. For example, Illinois public schools have mandated the inclusion of LGBTQ+ history in their curriculum, ensuring accurate representation despite external pressures. ​ axios.com  These initiatives collectively promote an inclusive and supportive educational environment, addressing the unique challenges faced by LGBTQIA+ student leaders.
Keywords: lgbtqia+; gender identity; social support; mental well-being; discrimination; identity struggles; inclusivity; gender diversity; and acceptance.